Theoretical and experimental approaches to determine the mass transfer coefficient in the steel/slag/refractory system - M Schickbichler; E Karimi-Sibaki; A Kharicha; S K. Michelic (The Australasian Institute of Mining and Metallurgy, 2024)
The requirements for the controllability of metallurgical processes are increasingly becoming the focus of both industry and research. Advances in this field of research not only impact the stability of processes but often also influence the quality of the final product. One important way to examine processes in-depth, and thus show potential for improvement, is to describe them using physicsdriven models. In metallurgy, thermodynamic and kinetic descriptions of interactions between individual components of a system are often used to describe and analyse important metallurgical phenomena across the entire process. However, for the creation of physics-based models, boundary conditions and process variables must be implemented to enable a description that is as realistic as possible. The collection and generalisation of boundary conditions and process variables is, therefore, an important step towards functional models. The focus of this study is the determination of mass transfer coefficients between all components in a steel/slag/refractory system. For this purpose, experimental and theoretical methods are applied. Laboratory scale experiments are carried out in an induction furnace, and the mass transfer coefficients of the defined steel/slag/refractory system are calculated from changes in the chemical composition of the various components. Additionally, a calculation of the mass transfer coefficients based on dimensionless quantities is carried out. By comparing the values of the mass transfer coefficients determined theoretically and those determined experimentally in the trials, the suitability of the calculation is examined. The collection of mass transfer coefficients provides essential findings for future kinetic descriptions of inclusion modification based on the effective equilibrium reaction zone (EERZ) approach.